Efficacy and safety of a new hyaluronic acid filler for nasolabial folds: A 52‐week, multicenter, randomized, evaluator/subject‐blind, split‐face study - Cheon, Hye In; Kim, Jin Hee; Kim, Beom Joon; Lee, Yang Won (Journal of cosmetic dermatology, 2021)
Background Hyaluronic acid fillers are known to be effective for correction of nasolabial folds. Recently, a novel biphasic hyaluronic acid filler incorporating lidocaine, DIVAVIVA medium has been introduced. Objectives We compared the efficacy and safety between DIVAVIVA medium and Restylane Perlane Lidocaine for moderate to severe nasolabial folds. Methods This was a multicenter, randomized, evaluator/subject‐blind, active‐controlled, split‐face study. A study 1 evaluated the efficacy and safety until 24 weeks. Extension study, study 2, included subjects who wanted to enroll and evaluated the efficacy and safety until 52 weeks. The Wrinkle Severity Rating Scale (WSRS) score, Global Aesthetic Improvement Scale, and Visual Analogue Scale measuring pain were evaluated. All adverse events were monitored. Results The mean change of WSRS at week 24 was −0.61 ± 0.54 in DIVAVIVA medium group and −0.59 ± 0.49 in Restylane Perlane Lidocaine group. The difference between two groups was 0.08, which was lower than noninferior limit. In study 2, the mean change of WSRS score at week 52 from baseline was −0.01 ± 0.62 in DIVAVIVA group, 0.06 ± 0.57 in Restylane Perlane Lidocaine group. The primary and secondary efficacy outcomes were also achieved in study 1 and 2. There was no significant difference in the incidence of adverse events between the two groups. Conclusion DIVAVIVA medium has comparable efficacy and safety with Restylane Perlane Lidocaine for correction of moderate to severe nasolabial folds.